2018
DOI: 10.1101/374264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent evolution of effector protease recognition by Arabidopsis and barley

Abstract: The Pseudomonas syringae cysteine protease AvrPphB activates the Arabidopsis resistance protein RPS5 by cleaving a second host protein, PBS1. AvrPphB induces defense responses in other plant species, but the genes and mechanisms mediating AvrPphB recognition in those species have not been defined. Here, we show that AvrPphB induces defense responses in diverse barley cultivars. We show also that barley contains two PBS1 orthologs, that their products are cleaved by AvrPphB, and that the barley AvrPphB response… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 66 publications
(95 reference statements)
1
31
0
Order By: Relevance
“…Neither fragment of PBS1 is sufficient to activate RPS5, although co‐expression of both fragments is required (DeYoung et al , ). Recently, it was shown that a barley NLR, PBR1 (AVRPPHB RESISTANCE 1), recognizes AvrPphB‐directed cleavage of PBS1 (Carter et al , ). However, in comparison with RPS5, the mechanistic basis of PBR1 recognition of processed PBS1 is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Neither fragment of PBS1 is sufficient to activate RPS5, although co‐expression of both fragments is required (DeYoung et al , ). Recently, it was shown that a barley NLR, PBR1 (AVRPPHB RESISTANCE 1), recognizes AvrPphB‐directed cleavage of PBS1 (Carter et al , ). However, in comparison with RPS5, the mechanistic basis of PBR1 recognition of processed PBS1 is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…PBS1 is highly conserved in both dicots and monocots (Caldwell and Michelmore 2009;Swiderski and Innes 2001), and many crop species are already resistant to Pseudomonas syringae through the recognition of AvrPphB, suggesting that they possess a functional analog of RPS5 (Carter et al 2019;Russell et al 2015). Indeed, we have recently shown that soybean, barley, and wheat all respond to AvrPphB protease activity (Carter et al 2019;Helm et al 2019) and this response in barley is mediated by a disease resistance protein designated Pbr1 (Carter et al 2019). Barley contains two PBS1 orthologs, both of which are cleaved by AvrPphB, and it is interesting to note that, while Pbr1 appears to monitor barley PBS1 orthologs in a way that is analogous to RPS5, RPS5 and Pbr1 are not orthologous (Carter et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have recently shown that soybean, barley, and wheat all respond to AvrPphB protease activity (Carter et al 2019;Helm et al 2019) and this response in barley is mediated by a disease resistance protein designated Pbr1 (Carter et al 2019). Barley contains two PBS1 orthologs, both of which are cleaved by AvrPphB, and it is interesting to note that, while Pbr1 appears to monitor barley PBS1 orthologs in a way that is analogous to RPS5, RPS5 and Pbr1 are not orthologous (Carter et al 2019). This suggests that the R protein involved in AvrPphB recognition has evolved convergently across species, whereas PBS1, the target of AvrPphB, appears to remain the same.…”
Section: Discussionmentioning
confidence: 99%
“…phaseolicola, a pathogen of common bean (Phaseolus vulgaris), based on its ability to induce resistance responses in specific bean cultivars (44). It has subsequently been shown to induce resistance responses in diverse crop species, including soybean, barley, and wheat (16,39,85). In all cases, protease activity is required to activate resistance responses, suggesting that all of these crops express a disease resistance protein that is activated by cleavage of an AvrPphB substrate.…”
Section: Translation To Crop Speciesmentioning
confidence: 99%
“…Barley contains two PBS1 orthologs, both of which are cleaved by AvrPphB (16). In addition, AvrPphB induces an HR in barley when delivered by a P. syringae strain that has had all its native effectors eliminated (strain DC3000 D36E).…”
Section: Translation To Crop Speciesmentioning
confidence: 99%